2019
DOI: 10.1021/jacs.9b03227
|View full text |Cite
|
Sign up to set email alerts
|

Micrometer-Sized Water Droplets Induce Spontaneous Reduction

Abstract: Bulk water serves as an inert solvent for many chemical and biological reactions. Here, we report a striking exception. We observe that in micrometer-sized water droplets (microdroplets), spontaneous reduction of several organic molecules occurs, pyruvate to lactate, lipoic acid to dihydrolipoic acid, fumarate to succinate, and oxaloacetate to malate. This reduction proceeds in microdroplets without any added electron donors or acceptors and without any applied voltage. In three of the four cases, the reductio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

16
303
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 275 publications
(321 citation statements)
references
References 40 publications
16
303
0
2
Order By: Relevance
“…It is known that a higher H + concentration could facilitate acid hydrolysis of proteins and a higher OH − concentration would promote trypsin activity. The value of the surface potential at the air-water interface is still debatable and estimated to be on the order of tens of megavolts per centimeter 56 . A potential of approximately 3 V across the 5 Å air-water interface 57,58 exceeds a standard potential of 1.23 V for the electrolysis of water molecules.…”
Section: Discussionmentioning
confidence: 99%
“…It is known that a higher H + concentration could facilitate acid hydrolysis of proteins and a higher OH − concentration would promote trypsin activity. The value of the surface potential at the air-water interface is still debatable and estimated to be on the order of tens of megavolts per centimeter 56 . A potential of approximately 3 V across the 5 Å air-water interface 57,58 exceeds a standard potential of 1.23 V for the electrolysis of water molecules.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, it has been proposed that as the size of a water microdroplet decreases, water molecules at and near the air-water interface autoionize more readily into H + and OH À than in bulk water. 55 This strong electric eld formed at the airwater interface is expected to promote the reduction of AuCl 4…”
Section: Possible Mechanism For Au-(his) 2 Formationmentioning
confidence: 99%
“…† As the temperature was increased from 30 C to 50 C, the average droplet size decreased from 6.9 mm to 5.4 mm, which is closer to the microdroplet size (2-3 mm) in ESI. Previous reports 39,55,56 have indicated that the droplet size has a large effect on the reaction rate in microdroplets; thus we speculate that the increased reaction rate in HUN at higher temperature is caused by the smaller droplet size. The following three reactions were also conducted at 50 C. The reaction in the nebulization cell is accelerated by the continuously atomized microdroplets from the reactant solution.…”
Section: Resultsmentioning
confidence: 54%